2012
DOI: 10.1186/1471-2202-13-144
|View full text |Cite|
|
Sign up to set email alerts
|

Wnt3a induces exosome secretion from primary cultured rat microglia

Abstract: BackgroundMicroglia, the immune effector cells of the CNS and the signaling molecule Wnt, both play critical roles in neurodevelopment and neurological disease. Here we describe the inducible release of exosomes from primary cultured rat microglia following treatment with recombinant carrier-free Wnt3a.ResultsWnt3a was internalised into microglia, being detectable in early endosomes, and secreted in exosomes through a GSK3-independent mechanism. Electron microscopy demonstrated that exosomes were elliptical, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 46 publications
0
89
0
Order By: Relevance
“…In addition, microglial exosomes are released in response to WNT3A, which is internalized and in turn stimulates the release of exosomes containing WNT3A. WNTs are signaling factors that have been implicated in several neurodegenerative diseases, such as Alzheimer disease (AD), suggesting that microglial exosomes regulate their pathologic development (49).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, microglial exosomes are released in response to WNT3A, which is internalized and in turn stimulates the release of exosomes containing WNT3A. WNTs are signaling factors that have been implicated in several neurodegenerative diseases, such as Alzheimer disease (AD), suggesting that microglial exosomes regulate their pathologic development (49).…”
Section: Discussionmentioning
confidence: 99%
“…Exosome cargo composition is highly affected by cellular homeostasis and pathology (Hooper et al 2012; Prieto et al 2017; Selmaj et al 2017; Wahlund et al 2017). As discussed in this review, toxic Aβ peptides and toxic species of P-Tau, neuroinflammation, and oxidative stress can all alter exosome content, secretion rate, and the cell-to-cell messages they carry.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that neuro-derived exosomes carrying specific types of miRNAs can activate Toll-like receptors (TLRs) and thus trigger inflammation signaling in the brain either in neighboring cells or during long-distance cell-to-cell communication via exosome transport in the extracellular matrix (Paschon et al 2016). Studies have also shown that activation of microglia, for example by the presence of amyloid, increases the release of exosomes, which may then directly participate in the inflammatory process in the brain (Hooper et al 2012). A recent study demonstrated that patients with lupus had increased exosomes in plasma compared to healthy controls, and when the lupus-originating exosomes were used to stimulate healthy peripheral blood mononuclear cells, this gave rise to a significant increase in IFN-α, TNF-α, IL-1β, and IL-6 compared to the stimulation obtained from healthy exosomes (Lee et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Stained bands corresponding to ~65kDa and ~75kDa FOXP1 proteins were excised, subjected to reduction, alkylation and trypsin digestion, and resulting peptides identified by mass spectrometry as previously described 36 with formic acid modified to 0.1% in the gradient.…”
Section: Mass Spectrometrymentioning
confidence: 99%